Depthwise distribution of available nutrients under plantations of multipurpose tree species - Singh, Sunpreet; Singh, Baljit (Indian Journal of Agroforestry, 2020)
A study was conducted to evaluate the effect of different tree species on available macro (N, P and K) and micro-nutrients (Fe, Mn, Cu and Zn) in soil after their long-term planting. Depthwise (0-15, 15-30, 30-45 and 45-60 cm) soil samples were taken from 20-years old plantation of eucalyptus (Eucalyptus tereticornis), neem (Azadirachta indica), dek (Melia azedarach), subabul (Leucaena leucocephala), shisham (Dalbergia sissoo), kikar (Acacia nilotica) and siris (Albizia lebbeck) spaced at 6 m Ã— 3 m and adjoining open area (control). The mean height of tree species ranged from 12.7 (shisham) to 25.8 m (eucalyptus) whereas mean diameter at breast height (DBH) ranged from 20.5 (shisham) to 33.9 cm (siris). Available N was higher under leguminous tree species (subabul, shisham, kikar and siris) than other species and control. Available P and K were highest under kikar (29.17 and 580 kg ha-1, respectively) in 0-15 cm soil depth. DTPA extractable Fe, Mn, Cu and Zn were also significantly higher under trees than control in 0-15 and 15-30 cm soil depths. Subabul and kikar had higher content of micro-nutrients in the soil than other tree species. Macronutrients as well as micro-nutrients decreased with increase in soil depth under all the tree species and control.